2017
DOI: 10.1038/s41467-017-00952-3
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control boosts glucosylated nanocarrier crossing the BBB into the brain

Abstract: Recently, nanocarriers that transport bioactive substances to a target site in the body have attracted considerable attention and undergone rapid progression in terms of the state of the art. However, few nanocarriers can enter the brain via a systemic route through the blood-brain barrier (BBB) to efficiently reach neurons. Here we prepare a self-assembled supramolecular nanocarrier with a surface featuring properly configured glucose. The BBB crossing and brain accumulation of this nanocarrier are boosted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 35 publications
9
207
0
Order By: Relevance
“…To this extent, the use of super-resolution imaging in combination with molecular dynamics simulation presents a critical role of the cargo in templating the tubular formation and dynamics (Fig.7). In conclusion, we shed light on BEC transcytosis using LRP1 as the main actor, but considering that "Goldilocks" avidity effect was also reported for transferrin receptor [49,50,51] and GLUT1 [52], our findings might suggest similar mechanisms. Nevertheless, ultimately, we report here a clear path to the brain, which once optimised it allows high delivery efficiency.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…To this extent, the use of super-resolution imaging in combination with molecular dynamics simulation presents a critical role of the cargo in templating the tubular formation and dynamics (Fig.7). In conclusion, we shed light on BEC transcytosis using LRP1 as the main actor, but considering that "Goldilocks" avidity effect was also reported for transferrin receptor [49,50,51] and GLUT1 [52], our findings might suggest similar mechanisms. Nevertheless, ultimately, we report here a clear path to the brain, which once optimised it allows high delivery efficiency.…”
Section: Discussionsupporting
confidence: 61%
“…Both methods show that while all angiopep-2 formulations enter the brain and can be found at relatively high concentrations across the BBB, the formulation with the most effective crossing is again A 22 -P, in agreement with the in vitro data. Such a non-linear dependence of the ligand binding energy on BBB crossing rate was also reported for the targeting of the transferrin receptor [49,50,51] and glucose transporter-1 (GLUT1) [52].…”
Section: Figurementioning
confidence: 54%
“…Hopefully, nanoparticle by intracephalic administration may be a method to resolve the problem. [16][17][18][19][20] It is a new idea for GBM treatment in future to lucubrate new intracephalic delivery carriers including nanoparticle and utilize their unique surface properties, good biocompatibility and biodegradation. In that way, we can achieve the goals to carry antitumor medicine through BBB or BTB to reach the target region of neoplasm and release drug continuously, eventually attaining drug concentration needed to inhibit or kill tumor cells and reducing the drug's toxicity to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…An in vivo study showed this drug delivery system could accumulate in brain tumors and substantially slow tumor growth. Glucose is another targeting ligand that could cross the brain capillary endothelial cells via glucose transporter-1 99 . Anraku et al 99 showed that glucose-modified nanocarriers could cross the BBB and accumulate in brain parenchyma, which has huge potential for the treatment of CNS diseases.…”
Section: Non-viral Gene Delivery To the Cns And Brain Tumorsmentioning
confidence: 99%